Utilization of Satellite Landsat-8 Operational Land Imager (OLI) for Land Cover Classification Nutmeg Plantation In Tapaktuan Sub-District - Safridatul Audah; Nazliyati Nazliyati (LPPM Politeknik Aceh Selatan, 2018)
This research seeks to utilize technology remote sensing with satellite Landsat 8 OLI imagery by classification method to obtain the area of ​​land cover used for nutmeg plantations in Tapaktuan Sub District. Several stages of image data processing methods have been done such as geometric correction of images, image cropping and image clsification.The result of geometric correction of image obtained RMS error of 0.011235 pixel, The geometric correction process has met the tolerance limit error > 1 pixel. As for the results of classification processing image Landsat-8 OLI year 2017 in Tapaktuan sub-district produce 6 classes land cover of nutmeg garden, mixed florest blantations,water, protected forest, settlement, and open land, the of classification results obtained by plantation area of nutmeg 4.72%, Based on the calculation of confusion matrix then obtained the overall accurasy value of 97.5714% and kappa accurasy of 96.55%. The result of classification accuracy test shows high accuracy and fulfill the requirement set by USGS (> 85%). This result shows that the map of Landsat-8 OLI image classification can be used as a material in determining the location of nutmeg plantation distribution.